(untitled) (Faridpur Medical College Journal, 2018)
Cervical cancer continues to be a major public health problem in Bangladesh in the absence of satisfactory and organized cervical screening programs. World Health Organization (WHO) considered cervical cancer as a preventable disease, as it can be identified in the pre-invasive stage. Visual inspection of the cervix with acetic acid (VIA) is an effective, inexpensive screening test that can be combined with simple treatment procedure for early cervical lesions, provided by trained health workers. To evaluate the value of visual inspection with acetic acid (VIA) for early detection of cervical pre-cancer and cancer in low resource country like Bangladesh, diluted acetic acid 5% was applied to the cervix and visual inspection was done. VIA tests were done for at least 3 years interval, in case of married woman, for cervical cancer screening. Women with positive results were sent for colposcopy. From January to December 2014, in Gynae OPD of the Faridpur Medical College Hospital, Faridpur, a total of 2000 women were screened by VIA test. Fourty-one VIA positive cases were identified and referred for colposcopy. Out of 41 cases, 27 patients underwent colposcopic examination, among them CIN-1 was found in 21 cases, CIN-2 in 2 cases and CIN-3 in 2 cases. However, two cases were colposcopically negative. So even during gynecological practice, if we arrange a setup for cervical screening by VIA test, many women can be saved from future development of carcinoma cervix later in their lives. Faridpur Med. Coll. J. Jan 2018;13(1): 24-27